Business Administration and Business Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
This study investigates the impact of Corporate Social Responsibility on profitability with particular reference to the Nigeria financial services industry. The study employed a survey research design. Primary data were collected using validated and reliable questionnaire instrument from sampled managers of Nigeria financial Services industry in Sagamu, Ogun State and were found usable. A sample size of 140 questionnaires was administered in this study. Correlation analysis was employed as a statistical technique to analyze data collected using SPSS 17.0. The results revealed that corporate social responsibility has a significant association with profitability. The study concludes that Nigeria financial Services industry should recognize the importance of corporate social responsibility for sustainable development as they perform their obligations to the society. And therefore, recommended that management of Nigeria financial Services industry should continue support CSR activities because any organization that does not invest much in corporate social responsibilities its long run existence is threaten.